Reciprocal regulation between B lymphoma Mo-MLV insertion region 1 homolog and type I insulin-like growth factor receptor in pemetrexed-resistant lung cancer cells - Huan-Ting Shen; Peng-Ju Chien; Gwo-Tarng Sheu; Bing-Yen Wang; Wen-Wei Chang (Tzu Chi Medical Journal, 2025)
Objectives: The objective of this study was to investigate the role of type I insulin-like growth factor receptor (IGF-1R) in pemetrexed-resistant lung cancer cells and its interaction with B lymphoma Mo-MLV insertion region 1 homolog (BMI1), previously identified as a key resistance gene. Materials and Methods: The study started with the analysis of the activation of IGF-1R in pemetrexed-resistant A549 (A400) lung cancer cells by Western blot analysis of its form of phosphorylation. Cancer stem cell (CSC) activity was assessed by tumor sphere culture. IGF-1R inhibition was performed by picropodophyllin (PPP), an IGF-1R inhibitor, or by shRNA-mediated RNA silencing. A Nonobese diabetic/severe combined immunodeficiency (NOD/SCID) mouse xenograft model was used to access in vivo pemetrexed sensitivity. To further understand the relationship between IGF-1R and BMI1, both BMI1 knockdown and overexpression experiments were performed to assess IGF-1R phosphorylation by western blot. Results: Increased IGF-1R phosphorylation was found in A400 cells, and subsequent IGF-1R inhibition resulted in a reduction in CSC activity in these resistant cells. In the in vivo studies, PPP treatment effectively suppressed tumor growth and reduced BMI1 expression in A400 tumor tissue. Further investigation showed that BMI1 knockdown in A400 cells resulted in decreased IGF-1R phosphorylation, whereas BMI1 overexpression in A549 cells resulted in increased IGF-1R phosphorylation, indicating an interaction between these two proteins. Conclusion: A novel reciprocal regulatory relationship between IGF-1R and BMI1 has been identified in lung cancer cells, suggesting potential therapeutic strategies to combat pemetrexed resistance in lung cancer patients.